Killing Gunther [videorecording (DVD)] - Killam, Taran; Killam, Taran; Moynihan, Bobby, 1977-; Simone, Hannah, 1980-; Smulders, Cobie, 1982-; Tolman, Allison; Gaul, Ryan, 1973-; Yoo, Aaron, 1979-; Brittain, Paul, 1977-; Talai, Amir, 1977-; Kelamis, Peter, 1967-; Schwarzenegger, Arnold (Lionsgate, 2017)
A group of assassins decide to kill Gunther, the world's greatest hit-man, but their plan turns into a series of fumbled encounters as Gunther seems to always be one step ahead.